KEAHLIAN AUDITOR DAN TURNOVER INTENTION SEBAGAI MEDIASI DETERMINAN KINERJA AUDITOR - Srimindarti, Ceacilia; Hardiningsih, Pancawati; Oktaviani, Rachmawati Meita (Jurnal Akuntansi dan Keuangan Indonesia, 2015)
This research aims to examine the effect of locus of control and organizational commitment on auditors’ performance as well as to examine whether auditors’ expertise and turnover intention mediate the effect of locus of control and organizational commitment on auditors’ performance. Samples of this study were auditors who worked at audit firms in Semarang. Samples were selected using the purposive sampling method. The data were analyzed using SEM with AMOS program. This study found that locus of control had a negative effect on auditors’ performance, organizational commitment had a positive effect on auditors’ performance, and auditors’ expertise and turnover intention had no effect on auditors’ performance. Furthermore, locus of control had a negative effect on auditors’ expertise, and organizational commitment had a negative effect on turnover intention. Based on this result, managers of public accounting firm (partners) should provide some trainings to the auditors who had the external locus of control so that they can achieve the standardized performances. They should also confirm the company’s values to the auditor to increase emotional attachment to the company as well as try to comply to the demands of the company thus its performance will be in accordance with company’s expectations.